2020
DOI: 10.3390/children7060063
|View full text |Cite
|
Sign up to set email alerts
|

Infant Care Practices among Resettled Refugee Mothers from East and Central Africa

Abstract: Refugees often parent under extreme circumstances. Parenting practices have implications for child outcomes, and parenting in the context of refugee resettlement is likely to be dynamic as parents negotiate a new culture. This study examined African origin mothers’ infant care values and practices related to feeding, carrying, and daily activities following resettlement in the Southeastern region of the U.S. Ten African origin mothers were asked about their infant care practices through semi-structured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 76 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…In the absence of extended family, many women sought support, friendship and advice from those from the same country of origin ( Russo et al., 2015 ; Bader et al., 2020 ; Kingsbury et al., 2018 ). However, issues of privacy within communities were often cited as a concern, specifically relating to violence, depression and HIV status ( Chulach et al., 2016 ; Ahmed et al., 2017 ; Yelland et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of extended family, many women sought support, friendship and advice from those from the same country of origin ( Russo et al., 2015 ; Bader et al., 2020 ; Kingsbury et al., 2018 ). However, issues of privacy within communities were often cited as a concern, specifically relating to violence, depression and HIV status ( Chulach et al., 2016 ; Ahmed et al., 2017 ; Yelland et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…A dichotomy emerged between satisfaction and lived experiences of maternity care. Many women who had migrated to high- or middle-income countries expressed satisfaction with their maternity care overall, but this was usually framed in contrast to their previous maternity experiences in resource-poor settings with higher maternal mortality rates and gratitude for being taken care of within the host country health system ( Riggs et al., 2017 ; Niner et al., 2013 ; Korukcu et al., 2018 ; Henry et al., 2020 ; Bader et al., 2020 ; LaMancuso et al., 2016 ). In spite of this satisfaction, women in many studies identified being stigmatised and receiving disrespectful or discriminatory care, due to being foreign, their skin colour, immigration status or being unable to speak the host-country language ( Riggs et al., 2017 ; Chulach et al., 2016 ; Niner et al., 2013 ; McLeish, 2005 ; Lalla et al., 2020 ; Herrel et al., 2004 ; Agbemenu et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the benefits of breastfeeding to the health and development of infants, providing culturally relevant education on breastfeeding is important to improve breastfeeding-related outcomes among resettled refugee populations ( 15 , 16 ). In Embrace's Healthy Babies and Breastfeeding module, community liaisons teach women about the health benefits of breastfeeding and navigating challenges with breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with U.S.-born and non-refugee immigrant women, refugee women begin prenatal care later and have fewer prenatal visits during pregnancy due to socioeconomic and language barriers, stigma, culturally insensitive health services, and other challenges (1,(4)(5)(6)8). Additionally, a number of studies have shown that refugee women have higher rates of labor induction and cesarean delivery (2,14), higher risk of preterm birth (1,2), lower birthweight babies (1,3), and lower rates of exclusive breastfeeding (15,16). Although, notably, some studies have shown inconsistent results-for example, well-documented advantages in birth outcomes for foreignborn Latina women relative to U.S.-born women (17) and other studies that found African refugee women have better pregnancy outcomes than U.S-born women.…”
mentioning
confidence: 99%